KEUNGGULAN BERSAING BISNIS PENDIDIKAN NON-FORMAL DI JAKARTA - Astuti, Miguna (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
The fundamental problem that led to this study is the limited empirical knowledge about non-formal education SMBs in Indonesia generally and in Jakarta especially, which makes the development of adapted theories and their successful implementation difficult. The non-formal education SMBs more known as ‘courses’. The paper addresses three specific problems: competitive advantage of courses and the impact of reputation and customer relationship factors on it.The specific goals and contributions of the research: (1) identifying customers’ perception on reputation of courses in Jakarta (2) identifying customers’ perception on customer relationship of courses in Jakarta (3) identifying customers, perception on competitive advantage of courses in Jakarta, and (4) analyzing the effect of reputation and customer relationship on competitive advantage of courses in Jakarta.The research methods used are explanatory and descriptive surveys using simple random. The data collecting technique used are literatures studies, observations, and questionnaires. The result of the collected data with the primary data source was received in form of number of sample of 135 respondents, in this case were students of 21 courses in Jakarta.The findings are: (1) Reputation perceived as average by customer (2) Customerrelationship perceived as average by customer, while (3) Competitive Advantage perceived as above than average by customer, (4) Reputation and customer relationship together have an influence on competitive advantage of courses in Jakarta, while individually reputation have no significant effect on reputation of courses in Jakarta.